Perancangan Media Pembelajaran Interaktif Konsep Dasar Seluler Menggunakan Aplikasi Unity Berbasis Android - Dio Alvendri; Yasdinul Huda; Resmi Darni (Journal on Education, 2023)
Telecommunication is the most important thing in this era of globalization, there are many ways to transfer information both conventionally and with the help of technology, the use of technology can be online or offline in the current era of digitalization, there have been many developments in telecommunication networks passed, the development of this cellular network has evolved from 1G, 2G, 3G even 4G, the "G" in 1G to 4G now refers to the term "generation". What is meant by generation here is the generation of wireless data and communication service technology, especially for mobile phones, because mobile social media users worldwide have increased rapidly from year to year. Android technology as a tool to use it. Interactive learning media are considered more effective in conveying material to students because students actively use interactive learning media to study the information in it. curriculum and seem too simple so that the educational program is not achieved. Using the Unity application in making Android-based interactive learning media is a form of learning that supports learning in the 21st century, especially the use of software. Of course, we need software to make a game. One of the software that can be used to make games is Unity. Unity is a cross-platform game engine designed to be easy to use. Like making a game that can be run on a computer. The material presented is in the form of general architecture of cellular systems using Unity.